Effects of Long-Term Exposure to PM2.5 on Oxidative Stress Injury and Expression of Inflammatory Factors, NF-κB p65 and Cx43 in Bone Marrow of Mice - Liu, Li-Li; Yang, Jing; Ye, Zhong-Lv; Tian, Chuan; Huang, Xiu-Lan; Zhang, Hui-Qin; Mo, Xiao-Huan (Frontiers in Environmental Science, 2022)
Objective: This study aims to explore the toxic effect of PM2.5 on the hematopoietic microenvironment of the bone marrow, and investigate the effect of PM2.5 on oxidative stress injury, the secretion of inflammatory cytokines and the expression of NF-κB p65 and Cx43 in the bone marrow of mice. Methods: A total of 615 mice were treated with normal saline, low dose (0.1 mg/ml) PM2.5 suspension, and high dose (0.2 mg/ml) PM2.5 suspension by intratracheal instillation, respectively. The ROS content, activity of total SOD (T-SOD), DNA injury, and the protein expression levels of IL-1 β, IL-6, TNF-α, NF-κB p65 and Cx43 in bone marrow cells (BMCs) of mice were detected in these three groups. Results: Compared with the normal saline control group, the expression level of reactive oxygen species (ROS) significantly increased in BMCs, while the activity of SOD enzymes significantly decreased in PM2.5 exposed mice. Furthermore, DNA injury significantly increased in PM2.5 exposed mice, and the expression of IL-1 β, IL-6, TNF-α and NF-κB p65 significantly increased, while the protein expression of Cx43 significantly decreased in the PM2.5 exposed mice. The differences were statistically significant (P<0.05). There were significant differences in ROS content, T-SOD activity, DNA injury (TL, TD and TM), protein expression of IL-1β, IL-6, TNF-α and Cx43 between the high-dose PM2.5 exposure group and low-dose PM2.5 exposure group (P<0.05), but there was no significant difference in the expression of NF-κB p65 between the high-dose and low-dose PM2.5 exposure groups (P>0.05). Conclusion: PM2.5 has toxic effects on the bone marrow of mice. Oxidative stress injury, inflammatory reaction and abnormal intercellular communication may be the underlying mechanism.